(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Measles remains to be a significant contributor to morbidity among young children all over the world, with the existence of effective vaccines. Improving vaccination strategies requires an understanding of the clinical and demographic characteristics of vulnerable children. This study aimed to assess the socio demo graphic patterns, clinical features and vaccination status of children under 5 years with measles in Chattogram, Bangladesh. Materials and methods: A descriptive cross-sectional study was conducted at the Department of Paediatrics, Chattogram Maa-Shishu O General Hospital from October 2020 to April 2021. Children aged 5 years and below with a history of measles were included based on WHO diagnostic criteria. A semi-structured questionnaire was used to collect data on age, sex, socioeconomic status and vaccination history. Data were analysed using SPSS version 22. Results: A total of 100 children were studied, with a mean age of 12.2 months with standard deviation (±5.7) months. The findings consisted of 67% boys and 33% girls. Most respondents lived in rural areas (58%) and had mothers with low education levels. All children presented with fever and rash, while 56% exhibited Koplik’s spots. Vaccination data showed that 69% had incomplete or no vaccination, with only 31% having completed two doses. Conclusion: The study emphasizes notable differences in children’s measles vaccination, especially in rural environments. Protecting these vulnerable groups and preventing future outbreaks depend on improving vaccination awareness and education. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 42-46